Human genetics : problems and approaches - Vogel, Friedrich; Motulsky, Arno G (Springer, 1996)
Institut fur Humangenetik und Anthropologie, Heidelberg, Germany. Third edition of an extensive textbook on the concepts and problems of human and medical genetics, for geneticists, biomedical researchers, physicians, and epidemiologists. Previous edition 1986. Emphasizes molecular concepts and techniques.
Keywords: lékařská genetika; genetika, lékařská genetika; Genetics, Medical